2013
DOI: 10.1097/mpg.0b013e31827e1ee2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High β‐Palmitate Content in Infant Formula on the Intestinal Microbiota of Term Infants

Abstract: HBP formula beneficially affected infant gut microbiota by increasing the Lactobacillus and bifidobacteria counts in fecal stools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
87
1
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(99 citation statements)
references
References 40 publications
2
87
1
9
Order By: Relevance
“…However, DXA measurements were available only for a sub-group of subjects, and bone mineral content of the radius obtained using single photon absorptiometry in all infants did not differ between groups (Kennedy et al, 1999). A small study (Yaron et al, 2013) evaluated the effect of formula with high sn-2 palmitate compared with a formula with low sn-2 palmitate on infant gut microbiota composition, reporting increases in Clostridium, Escherichia coli, Pseudomonas and Staphylococcus numbers, but only by plate counting and without providing further characterisation of the bacterial groups analysed to infer possible physiological/clinical consequences of the changes reported. One study which investigated the effect of sn-2 palmitate on blood lipids found lower high-density lipoprotein (HDL)-cholesterol and apolipoprotein A1 concentrations and higher apolipoprotein B concentrations in the group being fed high sn-2 palmitate formula (Nelson and Innis, 1999), but the relevance of this finding in infants is unknown.…”
Section: Molecular Speciation Of Fatty Acidsmentioning
confidence: 99%
“…However, DXA measurements were available only for a sub-group of subjects, and bone mineral content of the radius obtained using single photon absorptiometry in all infants did not differ between groups (Kennedy et al, 1999). A small study (Yaron et al, 2013) evaluated the effect of formula with high sn-2 palmitate compared with a formula with low sn-2 palmitate on infant gut microbiota composition, reporting increases in Clostridium, Escherichia coli, Pseudomonas and Staphylococcus numbers, but only by plate counting and without providing further characterisation of the bacterial groups analysed to infer possible physiological/clinical consequences of the changes reported. One study which investigated the effect of sn-2 palmitate on blood lipids found lower high-density lipoprotein (HDL)-cholesterol and apolipoprotein A1 concentrations and higher apolipoprotein B concentrations in the group being fed high sn-2 palmitate formula (Nelson and Innis, 1999), but the relevance of this finding in infants is unknown.…”
Section: Molecular Speciation Of Fatty Acidsmentioning
confidence: 99%
“…Protein, both its'source (whey, a-lactalbumin) and amount, lactose, low phosphor, iron and lipids (b-palmitate) are also bifidogenic. 8 Prebiotics and composition of GI microbiota Short-chain (sc) prebiotics are mainly fermented in the cecum and colon ascendens. Long chain (lc) OS are fermented along the entire colon.…”
Section: Prebiotics Gut Metabolic Activity and Bifidogenic Effectmentioning
confidence: 99%
“…However, compared with breastfed infants, the FF group stool in the early 3 months of life was less soft (ClinicalTrials.gov Identifier: NCT01157390). sn-2 palmitate, such as increasing beneficial gut flora [15,16] and reducing infant crying [17]. According to our knowledge, this is the first study examining an infant formula with milk fat, prebiotics and structured lipids.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was demonstrated in both preterm and term infants that by increasing the proportion of sn-2 position palmitate in the formula not only that the excretion of palmitate and associated calcium soaps in the stool is reduced and calcium absorption subsequently increased, but also stool hardness is reduced [14]. During the last years, the importance of a fat structure which is similar to that of human milk fat, was further revealed by additional benefits known for human milk, that were demonstrated for infant formula with high sn-2 palmitate, such as increasing beneficial gut flora [15,16] and reducing infant crying [17]. According to our knowledge, this is the first study examining an infant formula with milk fat, prebiotics and structured lipids.…”
Section: Introductionmentioning
confidence: 99%